History of Environmental Justice in Memphis's Lamar Avenue Corridor - Monfeli, Nick; Healy, Meg; Utebaliyeva, Maira; Greenstreet, Alexis (My University, 2013)
Lamar Avenue in Memphis, TN serves as a hub for industry and a convergence point for air, rail and freight traffic. The presence of the Memphis International Airport, the national headquarters of Federal Express, as well as dozens of factories and industrial plants has resulted in both crippling congestion and high levels of toxic emissions. Our research has analyzed the implications of this industry on the five adjacent residential neighborhoods. In addition to designing an interactive website that allows users to explore specific factors contributing to pollution and livability, our research has also sought to contextualize the current environmental issues facing the Lamar Avenue Corridor by researching the complex history of the area. This paper explores the dynamic history of Memphis, with particular emphasis on the city's role in the civil rights and environmental justice movements.
Includes Maps, Photographs, Drawings and Bibliography.
Keywords: Lamar Avenue Corridor; Environmental Justice; Memphis